2010
DOI: 10.1103/physrevc.81.044906
|View full text |Cite
|
Sign up to set email alerts
|

Eccentricity fluctuations in an integrated hybrid approach: Influence on elliptic flow

Abstract: The effects of initial state fluctuations on elliptic flow are investigated within a (3 + 1)-dimensional Boltzmann + hydrodynamics transport approach. The spatial eccentricity ( RP and part ) is calculated for initial conditions generated by a hadronic transport approach (ultrarelativistic quantum molecular dynamics). Elliptic flow results as a function of impact parameter, beam energy, and transverse momentum for two different equations of state and for averaged initial conditions or a full event-by-event set… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…This also holds for the flow coefficient v 5 which still is in line with the data within error bars. It is quite remarkable that the collective behavior is reproduced not only for semi-central collisions (lower part) but also for 0-5% central collisions (upper part) that are more sensitive to the initial fluctuations [23].…”
Section: Differential Flow Results For Pb-pbmentioning
confidence: 94%
See 1 more Smart Citation
“…This also holds for the flow coefficient v 5 which still is in line with the data within error bars. It is quite remarkable that the collective behavior is reproduced not only for semi-central collisions (lower part) but also for 0-5% central collisions (upper part) that are more sensitive to the initial fluctuations [23].…”
Section: Differential Flow Results For Pb-pbmentioning
confidence: 94%
“…in Refs. [23,26] have shown that the elliptic flow v 2 in semi-peripheral reactions is dominated by the geometry and less by the initial state fluctuations, however, central collisions do show a sensitivity to these fluctuations. The same arguments hold for v 4 which is roughly ∼ v 2 2 (cf.…”
Section: Probing the Initial Size Of Spatial Fluctuations With Phsdmentioning
confidence: 99%
“…There has been a significant effort recently in studying fluctuating initial conditions in heavy ion collisions [29][30][31][32][33][34] and studying their propagation in full fluid dynamic simulations or transport models [35][36][37][38][39][40][41][42][43][44]. Precursors of these developments include e.g.…”
Section: Jhep11(2011)100mentioning
confidence: 99%
“…In addition, widely held beliefs as to which moments of the initial eccentricity distribution are directly related to which moments of the final flow distribution [17,21,26] must be tested by generating the final states hydrodyamically event by event, i.e. separately for each fluctuating initial condition [20,[27][28][29][30][31]. These are the goals addressed in the present article.…”
Section: Introductionmentioning
confidence: 99%